The PI3K p110δ regulates expression of CD38 on regulatory T cells. - Daniel T Patton; Marcus D Wilson; Wendy C Rowan; Dalya R Soond; Klaus Okkenhaug (PLoS ONE)
The PI3K pathway has emerged as a key regulator of regulatory T cell (Treg) development and homeostasis and is required for full Treg-mediated suppression. To identify new genes involved in PI3K-dependent suppression, we compared the transcriptome of WT and p110δ(D910A) Tregs. Among the genes that were differentially expressed was the gene for the transmembrane cyclic ADP ribose hydrolase CD38. Here we show that CD38 is expressed mainly by a subset of Foxp3(+)CD25(+)CD4(+) T cells originating in the thymus and on Tregs in the spleen. CD38(high) WT Tregs showed superior suppressive activity to CD38(low) Tregs, which failed to upregulate CD73, a surface protein which is important for suppression. However, Tregs from heterozygous CD38(+/-) mice were unimpaired despite lower levels of CD38 expression. Therefore, CD38 can be used as a marker for Tregs with high suppressive activity and the impaired Treg function in p110δ(D910A) mice can in part be explained by the failure of CD38(high) cells to develop.